The effect of anti-lymphocytic antibody on the humoral immune response in different strains of mice: I. The response to bovine serum albumin - James, K. (1972)
The effect of a single batch of horse anti-mouse thymocyte globulin on the humoral immune response has been extensively investigated in 10–12-week-old male mice of six inbred strains. The preparation under test readily suppressed the primary immune response of A/HeJ, C57B1, DBA/1, CBA and C(3)H mice to 0.1, 1.0 and 10.0 mg doses of alum precipitated bovine serum albumin (alum BSA). However, at the doses used it generally failed to significantly suppress the primary immune response of BALB/c mice to 0.1 and 1.0 mg doses of this antigen. Furthermore, the effectiveness of the suppression was somewhat diminished by the incorporation of bordetella pertussis organisms into the alum BSA inoculum. The product also suppressed the secondary immune response to alum BSA in C(3)H mice and C57B1 mice but, at the same doses, was without significant effect on the secondary responses of A/HeJ and CBA mice.